Comparison of the corrosion behaviour of austenitic stainless steel in seawater and in a 3.5 % NaCl solution - Donik, Črtomir (Materiali in tehnologije, 2014)
The evolution of the passive films on austenitic AISI 316L stainless steel in seawater and in pure 3.5 % NaCl was studied using potentiodynamic (PD) measurements, X-ray photoelectron spectroscopy (XPS) and electrochemical impedance spectroscopy (EIS). This paper describes and evaluates the comparison of pure 3.5 % NaCl with seawater through surface and corrosion measurements. The formation of the passive film was studied by EIS at the open-circuit potential (OCP), by potentiodynamic measurements and by X-ray photoelectron spectroscopy, where their compositions were analysed as a function of depth, and the cationic fraction of the passive film was determined. The passive films on both materials predominantly contained Cr-oxides, whereas the Fe species were markedly depleted.
Keywords: nerjavno jeklo; stainless steel; XPS; potenciodinamske meritve; potentiodynamic measurements; pasivacija; EIS; passivity